2017
DOI: 10.1016/s2468-2667(17)30047-6
|View full text |Cite|
|
Sign up to set email alerts
|

Health consequences of the US Deferred Action for Childhood Arrivals (DACA) immigration programme: a quasi-experimental study

Abstract: SummaryBackground The effects of changes in immigration policy on health outcomes among undocumented immigrants are not well known. We aimed to examine the physical and mental health effects of the Deferred Action for Childhood Arrivals (DACA) programme, a 2012 US immigration policy that provided renewable work permits and freedom from deportation for a large number of undocumented immigrants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
154
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(157 citation statements)
references
References 31 publications
2
154
1
Order By: Relevance
“…22 This access to coverage, albeit limited, has been found to have a positive impact on the physical health outcomes of its recipients. 23 Having a legal presence has also helped to reduce DACA recipients' fear of seeing a doctor for check-ups or going to a hospital or clinic for treatment when necessary. 24 As a result, DACA recipients were able to receive improved treatment and preventive care.…”
Section: Journal Of Immigrantmentioning
confidence: 99%
“…22 This access to coverage, albeit limited, has been found to have a positive impact on the physical health outcomes of its recipients. 23 Having a legal presence has also helped to reduce DACA recipients' fear of seeing a doctor for check-ups or going to a hospital or clinic for treatment when necessary. 24 As a result, DACA recipients were able to receive improved treatment and preventive care.…”
Section: Journal Of Immigrantmentioning
confidence: 99%
“…In addition, research has shown that DACA increase the economic and social incorporation of recipients by allowing them increased opportunities to open bank accounts and obtain credit cards (Gonzales, Terriquez and Ruszczyk, 2014) and improves recipients' mental health (Venkataramani, et al 2017). …”
Section: Introductionmentioning
confidence: 99%
“…An estimated 200,000 children had parents who were eligible for DACA at the time the policy was announced (2). Although some studies have found that DACA recipients have higher rates of employment (2022) and improved health outcomes (23, 24), the intergenerational effects of DACA are largely unknown.…”
mentioning
confidence: 99%